KONTRIBUSI KELENTUKAN TUBUH DAN POWER OTOT TUNGKAI TERHADAP KEMAMPUAN MENGGIRING BOLA - Lalu Hulfian; Mujriah Mujriah (Universitas Pendidikan Mandalika, 2018)
The problem was the lack of ability of dribble on the players of Lombok Smile FC, which is clearly seen on his body flexibility and limb muscle power that is inadequate in performing dribble. The purpose of this research is to determine whether or no there is correlation between body flexibility and limb muscle power toward dribble ability in football on the Lombok Smile FC. The design of this type of research is correlation using Direct Correlation. The method used in this research is method of documentation and test methods. The sample in this research is 20 players using sampling techniques of study population. On a significant level of 5%, Ho is rejected and Ha is accepeted. This is because the number limit of rejected in r table = 0.444 at N = 20. While the r-score is 0.793 so that r-score is higher than the r-table on the 5% significance level (0.793 > 0.444). This means that the Ha is accepted which states; there is significant correlation between body flexibility and limb muscle power toward dribble ability.